The Cytotoxic Activity of Rosemary Essential Oil on PANC-1 Cells - Hoca, Mustafa; Becer, Eda; Yakubu, Abdussalam; Vatansever, Hafize Seda (Galenos Publ House, 2025)
BACKGROUND/AIMS: The goal of this research was to analyze the cytotoxic impacts of rosemary essential oil on pancreatic cancer. MATERIALS AND METHODS: The human pancreatic cancer cell line (PANC-1) was used. The leaves of rosemary cultivated in North Cyprus were collected during the flowering stage. Rosemary essential oil was obtained after air-dried leaves (100 g) were distilled with water for 3 hours. Rosemary essential oil solutions were prepared and diluted in culture medium using various concentrations (100, 200, 300, 400, 500, and 600 pM) for 24 hours and 48 hours incubation periods. The analysis of cytotoxicity was conducted using the MTT [3-(4,5-dimethylthiazol-2-yl)-2,5diphenyl tetrazolium bromide]. RESULTS: Rosemary oil at 500 mu M was more effective in diminishing the proliferation of PANC-1 cells than other concentrations during 48 hours. Cell viability was significantly greater at 100 pM for 24 hours (100%) than 600 pM for 48 hours (81.48%). It was determined that substantially greater cell viability was observed at 200 pM for 24 hours (97.05%) when compared to 600 pM for 48 hours (81.48%). In addition, when various concentrations were evaluated during 48 hours, significant differentiation was found between 100 pM and 600 pM. It was shown that there was a significant differentiation between 200 pM and 600 pM for 48 hours. CONCLUSION: Cell viability was substantially less at 600 pM than at 100 pM and 200 pM, 81.48%, 95.18%, and 90.23%, respectively.
Keywords: Cytotoxic; essential oil; pancreatic cancer; rosemary